Clinically oriented anatomy - Moore, Keith L.; Dalley, Arthur F.; Agur, Anne M. R. (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2014)
Clinically Oriented Anatomy provides first-year medical students with the clinically oriented anatomical information as it relates to the practice of medicine, dentistry, and physical therapy. The 7th edition features a fully revised art program to ensure consistency and cohesiveness of imaging style.